Are cardiovascular health measures heritable across three generations of families in Soweto, South Africa? A cross-sectional analysis using the random family method. Issue 9 (23rd September 2022) - Ware, Lisa J; Maposa, Innocent; Kolkenbeck-Ruh, Andrea; Norris, Shane A; Soepnel, Larske; Crouch, Simone; Kagura, Juliana; Naidoo, Sanushka; Smith, Wayne; Davies, Justine
Abstract : Objectives: Cardiovascular disease is increasing in many low and middle-income countries, including those in Africa. To inform strategies for the prevention of cardiovascular disease in South Africa, we sought to determine the broad heritability of phenotypic markers of cardiovascular risk across three generations. Design: A cross-sectional study conducted in a longitudinal family cohort. Setting: Research unit within a tertiary hospital in a historically disadvantaged, large urban township of South Africa. Participants: 195 individuals from 65 biological families with all three generations including third-generation children aged 4–10 years were recruited from the longest running intergenerational cohort study in Africa, the Birth to Twenty Plus cohort. All adults (grandparents and parents) were female while children were male or female. Primary and secondary outcome measures: The primary outcome was heritability of blood pressure (BP; brachial and central pressures). Secondary outcomes were heritability of arterial stiffness (pulse wave velocity), carotid intima media thickness (cIMT) and left ventricular mass indexed to body surface area (LVMI). Results: While no significant intergenerational relationships of BP or arterial stiffness were found, there were significant relationships in LVMI across all three generations (p<0.04), and in cIMT between grandparents and parents (p=0.0166). Heritability, the proportion of phenotypic trait variation attributable to genetics, was estimated from three common statistical methods and ranged from 23% to 44% for cIMT and from 21% to 39% for LVMI. Conclusions: Structural indicators of vascular health, which are strong markers of future clinical cardiovascular outcomes, transmit between generations within African families. Identification of these markers in parents may be useful to trigger assessments of preventable risk factors for cardiovascular disease in offspring.